From Readers to Educators: Shaping Literary Sensibility in Elementary Teachers Through a Structured Learning Model - Angga Warda Prasakti; Desti Angraini; Muhammad Ajmal; Yasir Riady; Ahmad Jum'a Khatib Nur Ali; Norizan Binti Baba Rahim (CV. Media Inti Teknologi, 2026)
Background: This study is grounded in the need for a literary learning approach that can develop students’ appreciation, aesthetic sensitivity, and critical understanding of literary works.Aims: This study aims to develop and examine the effectiveness of the literary appreciation learning model applied to students in the Elementary School Teacher Education Study Program (PGSD) at the Open University (UT), Jambi City.Methods: The research uses a descriptive qualitative approach with a case study method. Data were collected through observation, interviews, and documentation.Results: The results of the study show that the literary appreciation learning model, based on critical and collaborative reflection, is able to increase reading interest, analytical power, and interpretation ability of students' literary works. This model also can be used as an alternative approach to literary learning in higher education, particularly in the context of distance learning. The findings show that 90% of students accurately identified literary elements, 85% generated original creative responses, and 80% reported increased interest in literature.Conclusion: it can be concluded that the literary appreciation learning model based on critical and collaborative reflection is effective in increasing the ability and interest of PGSD students at the Open University of Jambi City in understanding and appreciating literary works.